Factors that affect cycling transportation mode for Postgraduate Students at Universiti Kebangsaan Malaysia by logit method - Sahar Abd Ali Dawood; Riza Atiq O.K. Rahmat (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
The main aim of this study is to investigate the factors that affect cycling transportation mode and give suggestions to encourage students to use these facilities to decrease the use of motorized transportation. Firstly we chose the Universiti Kebangsaan Malaysia (UKM) campus as an example for our study which focused on shifting from motorized transport to non-motorized especially to cycling transport. Our study involved conducting a survey on postgraduate students at 1st semester (2013-2014). A total of 169 questionnaires were distributed personally inside the campus and interviews were done with the students. Our survey showed that the majority of postgraduate students were tending to use car with percentage of 45.5% and 38.4% prefer using the bus followed by 12.4% using motorcycle and the least percentage using bicycles with percentage of 3.5%. The most effective factor in shifting postgraduate students who use cars and motorcycles to use bicycles is imposing fees on parking inside UKM and limiting the space for parking. The decrease in the number of buses inside campus and imposing fees on buses have high effectiveness in switching students who use the bus to cycling transportation.